2009
DOI: 10.1161/hypertensionaha.109.137471
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean-Style Diet Effect on the Structural Properties of the Erythrocyte Cell Membrane of Hypertensive Patients

Abstract: Abstract-A currently ongoing randomized trial has revealed that the Mediterranean diet, rich in virgin olive oil or nuts, reduces systolic blood pressure in high-risk cardiovascular patients. Here, we present a structural substudy to assess the effect of a Mediterranean-style diet supplemented with nuts or virgin olive oil on erythrocyte membrane properties in 36 hypertensive participants after 1 year of intervention. Erythrocyte membrane lipid composition, structural properties of reconstituted erythrocyte me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 31 publications
4
37
0
1
Order By: Relevance
“…This mechanism for the endogenous generation of a sEH inhibitor providing cardiovascular protection is fully consistent with the actions of synthetic sEH inhibitors (41,42). The findings of this study may provide an explanation, at least in part, for the findings of the Prevención con Dieta Mediterránea (PREDIMED) multicenter randomized trial (43), which showed a Mediterranean diet supplemented with extra virgin olive oil or nuts reduced the incidence of major cardiovascular events.…”
Section: Discussionsupporting
confidence: 82%
“…This mechanism for the endogenous generation of a sEH inhibitor providing cardiovascular protection is fully consistent with the actions of synthetic sEH inhibitors (41,42). The findings of this study may provide an explanation, at least in part, for the findings of the Prevención con Dieta Mediterránea (PREDIMED) multicenter randomized trial (43), which showed a Mediterranean diet supplemented with extra virgin olive oil or nuts reduced the incidence of major cardiovascular events.…”
Section: Discussionsupporting
confidence: 82%
“…This is the first study showing that in healthy adolescents, there is an inverse relation of KIDMED index with albuminuria. One could suggest that the protective to the endothelium and anti-atherosclerotic properties of the Mediterranean diet (Willett et al, 1995;Trichopoulou and Lagiou, 1997;Panagiotakos et al, 2003Panagiotakos et al, , 2007Psaltopoulou et al, 2004;Serra-Majem et al, 2004;Trichopoulos and Lagiou, 2004;Estruch et al, 2006;Karlin et al, 2008;Barceló et al, 2009; Nú ñez-Có rdoba et al, 2009) could be the pathophysiological explanation for the observed relation of the level of adherence to this favorable diet and decreased urinary albumin excretion. It is also established that the Mediterranean food pattern is related to reduced inflammatory activation (Carter et al, 2010) that in its own turn is associated with attenuated levels of albuminuria as previously shown (Tsioufis et al, 2004;Tsioufis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This has not been observed in the usually small-sized clinical studies performed to date, but the larger PREDIMED trial did show significant reductions in both systolic and diastolic blood pressure after the nut-supplemented Mediterranean diet compared with the control diet [80]. A recent report of the PREDIMED trial provides an insight into the possible mechanism of this antihypertensive effect by showing that the nut diet was associated with reduced cholesterol: phospholipid ratios of erythrocyte membranes, which would translate into an increase of membrane fluidity [128]. Possibly future adequately powered studies might uncover a true antihypertensive effect of nut intake.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 99%